Investigation of an Outbreak of Acute Gastroenteritis in Kollam, Kerala, India - P. S. Rakesh; Vishnu Narayanan; Swapna S. Pillai; Rahul Retheesh; Soumya Dev (Journal of Primary Care & Community Health, 2016)
An outbreak investigation was initiated following a report of unusual occurrence of acute gastroenteritis in Ashramam area, Kollam district, Kerala, India. House to house survey was conducted to identify cases. Person, place, and time analysis was done. Hypothesis was generated based on findings from cross sectional study, anecdotal evidences, laboratory investigation, and environmental observations. Univariate analysis was done generating odds ratios and confidence intervals to identify factors associated with the disease. A total of 57 cases were reported. Attack rate was highest among children younger than 14 years (22%). Among them, 91.2% (52/57) of the cases and 45.8% (169/369) of the people who had not developed the disease were dependent on pipe water (OR 12.31; 95% CI 4.81-31.52) for drinking purpose. The time frame of the disease occurrence, environmental observations, anecdotal evidences, and the results of analytical study indicated the possibility of the acute gastroenteritis outbreak as a result of pipeline contamination. The study warrants establishment of a good water quality surveillance system.